Minor Base Composition of “70S-Associated” 4S RNA from Avian Myeloblastosis Virus - Rosenthal, Leonard J. (1973)
Using a chemical isotope derivative method, we have determined the minor base composition of the “70S-associated” 4S RNA isolated from avian myeloblastosis virus. The minor base composition of this “70S-associated” 4S RNA is strikingly similar to that of the corresponding “free” 4S RNA of the virion. This minor base content, plus the capacity to esterify amino acids, establishes that both of these virion 4S RNA fractions contain transfer RNA. The percentage of minor bases in virion “70S-associated” 4S RNA is, however, much lower than in “free” 4S virion RNA and in myeloblast 4S RNA. The implication is that the “70S-associated” 4S RNA fraction as isolated herein also contains RNA that is not transfer RNA. This latter RNA may represent either degradation products of high molecular weight RNA or indigenous 4S RNA of undetermined function.